Comparison of cognitive workload and surgical outcomes between a three-dimensional and conventional microscope macular hole surgery - Aditya Kelkar; S. Natarajan; Akshay Kothari; Mounika Bolisetty (BMC Ophthalmology, 2024)
Abstract Background Performing a surgical task subjects the surgeon to multitudinal stressors, especially with the newer 3D technology. The quantum of cognitive workload using this modern surgical system in comparison to the Conventional microscope system remains unexplored. We evaluate the surgeon’s cognitive workload and the surgical outcomes of macular hole(MH) surgery performed on a 3D versus a Conventional microscope operating system. Methods 50 eyes of 50 patients with MH undergoing surgery using the 3D or Conventional microscope visualization system. Cognitive workload assessment was done by real-time tools(Surgeons’ heart rate [HR] and oxygen saturation[SPO2]) and self-report tool(Surgery Task Load Index[SURG-TLX] questionnaire) of three Vitreoretinal surgeons. Based on the SURG-TLX questionnaire, an assessment of the workload was performed. Results Of the 50 eyes, 30 eyes and 20 eyes underwent surgery with the Conventional microscope and the 3D system, respectively. No difference was noted in the MH basal-diameter(p = 0.128), total surgical-duration(p = 0.299), internal-limiting membrane(ILM) peel time(p = 0.682), and the final visual acuity (VA; p = 0.515) between the two groups. Both groups showed significant improvement in VA(p < 0.001) with a 90% closure rate at one-month post-surgery. Cognitive workload comparison, the intraoperative HR(p = 0.024), total workload score(P = 0.005), and temporal-demand dimension(p = 0.004) were significantly more in Conventional microscope group as compared to 3D group. In both the groups, the HR increased significantly from the baseline while performing ILM peeling and at the end. Conclusion The surgeon’s cognitive workload is markedly reduced while performing macular hole surgery with a 3D viewing system. Moreover, duration of surgery including ILM peel time, MH closure rates, and visual outcomes remains unaffected irrespective of the operating microscope system.